The potential, strategies, and challenges of Monascus pigment for food application - Egea, Mariana Buranelo; Dantas, Luciana Arantes; Sousa, Tainara Leal de; Lima, Alan Gomes; Lemes, Ailton Cesar (Frontiers in Sustainable Food Systems, 2023)
The demand for dyes from natural sources to substitute synthetic dyes for application in the food industry has been continuously increasing due to some synthetic dyes being associated with several problems, including hypersensitivity, carcinogenesis, and negative environmental impacts. Furthermore, dyes from natural sources (like pigments) are generally regarded by the consumer as safer or with fewer side effects—a fact that requires in-depth investigation—, which increases the commercial interest in such products. In this sense, great focus has been given to the biotechnological potential of Monascus sp. to produce red, orange, and yellow pigments using different types of the fermentation process (submerged or in solid-state fermentation), substrates, and process parameters (temperature, pH, agitation, aeration, etc.), aiming at optimizing and reducing costs in pigment production. In general, Monascus pigment has shown stability at neutral and basic pH, at elevated temperatures for a few hours, and to some metallic ions while not showing stability at acidic pH, elevated temperatures for many hours, and in the presence of light. Applications of Monascus pigment with colorant function in foods (candies, bread, yogurt, cheese, beer, and meat products) reported improvement in the color aspect by sensory analysis. The application of Monascus pigment still seems promising and incipient, demonstrating that it needs to be further studied, mainly concerning the stability of the pigment in vivo systems (inside the food) where adverse conditions are combined. Regulatory issues are heterogeneous around the world, which creates difficulties to expand production and commercialization but also demonstrates the need for studies to confirm its safety. In this sense, this mini-review presents the potential, strategies, and challenges of Monascus pigment for food application.